PARENTS’ INVOLVEMENT IN SEXUAL AND REPRODUCTIVE HEALTH EDUCATION FOR CHILDREN: A SCOPING REVIEW (Women, Midwives and Midwifery, 2021)
Background: Parents play important role  for educationg children about sexual and reproductive health. Sexual and reproductive health education is very important to be provided for children in early age, so that they could protect themselves from  sexual violence. However, the information about sexual and reproductive health should be taught by parents so that children do not misstep in their lives. Objective: to review the evidence of parenting involvement in adolescent sexual and reproductive health education. Methods: The method of scoping reviews have adopted the framework of Arksey and O'Malley (2005), the steps of framework are (1) The identification of scoping review questions, (2) The identification of relevant articles, (3) The selection of articles,  (4) Data Charting , (5) Maping, collating and summarizing. The writer searches for articles in 3 databases and selects the original article for review. The article theme focuses on the parents involvement in sexual and reproductive health education against children in developing countries that conducted in 2009-2019.  Findings: Out of the 8 selected articles. Five themes of scoping review are the factors that influence parent and child communication, such as age, gender, education, social, economic, generation and relationship of family gaps. The obstacle of providing reproductive health education and sexual in children due to parents are ashamed, uncomfortable , lack of knowledge , and the influence of culture and norms. HIV/AIDS is a topic that is often discussed by parents. Knowing about sex education is important for children, while parents and teachers are sources of this information. In order to teach sexual and reproductive health education well, parents need good communication and improve their knowledge.  Conclusion: In order to provide sexual and reproductive health education, there are several factors and barriers that affect the communication of parents and children. Parents only discuss sexual and reproductive health issues generally. They also teach their children about the dangers of premarital sex.